Pelatihan Pembukuan Sederhana dan Perhitungan Biaya Usaha untuk Penetapan Harga Jual pada UMKM di Kota Batam - Puspita Rama Nopiana; Fira Yuniar Fau; Krisdiana Wau (Jurnal Kabar Masyarakat, 2026)
MSMEs play a significant role in supporting regional economic development. However, many business owners still face challenges in financial management, particularly in maintaining simple bookkeeping, calculating business costs, and determining appropriate selling prices. These challenges were identified in Trend Accessories and Gift, a trading business, and Si Fang Yuan Dimsum, a culinary business, both located in Batam City. The two partner MSMEs had not implemented systematic financial records, resulting in business cost information that was not optimally utilized for pricing decisions. This community service program aimed to enhance the partners’ understanding of simple bookkeeping and business cost calculation as the basis for determining selling prices. The program employed a Participatory Action Research approach, consisting of problem identification, planning, training implementation, practical mentoring, monitoring, and evaluation. The training utilized a simple bookkeeping module and a Microsoft Excel-based bookkeeping template using the partners’ actual business transaction data. The results demonstrated that both partners gained a better understanding of preparing simple bookkeeping records, identifying business cost components according to the characteristics of their businesses, calculating the Cost of Goods Sold for the trading business and business costs for the culinary business, and utilizing cost information to establish more rational selling prices. Furthermore, the program increased the partners’ awareness of the importance of systematic financial recordkeeping as an essential component of sound business financial management. Overall, the training and mentoring activities contributed to strengthening the financial management capacity of the partner MSMEs and supported more effective, accountable, and sustainable business decision-making.